Age composition and feeding ecology of early juvenile Notothenia rossii (Pisces, Nototheniidae) at Potter Cove, South Shetland Islands, Antarctica - Barrera Oro, Esteban; Winter, Debora J. (Antarctic Science)
Age and diet of 140 brown phase early juvenile Notothenia rossii specimens caught at Potter Cove from December 2005–March 2006 were studied. Fish were immature, in the range 8.5–21 cm TL and of age groups 1–2 (otolith/scale readings). The diet (F% and coefficient Q methods) was mainly benthic-demersal organisms with Gammaridean amphipods (primarily Gondogeneia antarctica) as the most frequent (F% = 98) and main prey (Q% = 97). The occurrence of algae, gastropods and harpacticoid copepods was high, but these organisms were secondary or occasional food. The importance of other benthic (bivalves, polychaetes, isopods) and pelagic (ostracods, calanoids, hyperiid amphipods, krill) prey was very low. Preference of larger fish for larger prey was evident. Stomach fullness analysis showed high food availability during the sampling period. Young stages of N. rossii are demersal, preying mainly on gammarideans and other invertebrates of the benthic community associated with macroalgae beds. The almost complete lack of plankton components in the diet of early juvenile fish suggests they do not migrate vertically to feed. Fil: Barrera Oro, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ictiología; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Winter, Debora J. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ictiología; Argentina